Pemimpin Idaman Dalam Masyarakat Multikultural (Universitas Sebelas Maret, 2022)
This study aims to formulate indicators and characteristics of an effective leader and are desired by a multicultural society. This research is important to answer various problems or conflicts that occur in Indonesian society, especially social conflicts related to religion. Based on the existing literature, it is explained that the factors associated with effective multicultural leadership to deal with social conflict are personal identity, individual competence and individual experiences related to diversity. The method used in this article is through normative research or through literature searches such as books, journals, papers and other sources that are considered to be similar or relevant. The results of the research in this article indicate that factors related to multicultural leadership expected by society are one's innate nature, values that support diversity that are instilled early in a person and environmental factors that can provide experiences to increase cultural intelligence. In the indicators there are innate traits that are important to have, such as: patient, courageous, assertive and innovative.